Understanding the impact of train run-throughs on railway switches using finite element analysis. (April 2019) - Shih, JY; Hemida, H; Stewart, E; Roberts, C
Train run-throughs on railway switches is a special issue, where a train passes through non-trailable railway switches in the wrong direction. This has the potential to cause severe damage and can lead to derailment. In order to understand the impact of train run-throughs on railway switches, a three-dimensional finite element model using explicit analysis has been developed. A detailed switch model has been developed that includes all key components: stretcher bars, supplementary drive and point operating equipment. The model was validated through a specifically designed experiment where switch run-throughs were emulated on a real switch; a good agreement was found between the experimental data and the model. The model has been used to make an assessment of the locking mechanisms. The forces in each component have been assessed and investigated, and the observations of failure location and component during run-through analysis are indicated. During a run-through, the supplementary drive rod and stretcher bar encounter a significant plastic deformation, and it is recommended that they should be redesigned in order to avoid plastic behaviour.